2021
DOI: 10.1039/d0sm01654c
|View full text |Cite
|
Sign up to set email alerts
|

Using reactive dissipative particle dynamics to understand local shape manipulation of polymer vesicles

Abstract: Biological cells have long been of interest to researchers due to their capacity to actively control their shape. Accordingly, there is significant interest in generating simplified synthetic protocells that can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…As the integrated assumptions are paramount to accurate simulations, central to the success and accuracy of DPD simulations is the definition of the force fields. 304,305 Full atom and coarse-grained modeling are commonly implemented to analyze the resulting morphology of assembled macromolecules in addition to key interactions, making these simulations excellent tools to corroborate and expand on experimental characterization techniques. Some examples of the implementation with PAs include lysinecontaining amphiphiles (see Figure 10)MD simulations showed that the increase in charge not only decreased the size of the micelle, as corroborated by experimental results, but also led to the formation of fewer total micelles.…”
Section: Secondary Interactions Used To Tune Assembled Morphologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As the integrated assumptions are paramount to accurate simulations, central to the success and accuracy of DPD simulations is the definition of the force fields. 304,305 Full atom and coarse-grained modeling are commonly implemented to analyze the resulting morphology of assembled macromolecules in addition to key interactions, making these simulations excellent tools to corroborate and expand on experimental characterization techniques. Some examples of the implementation with PAs include lysinecontaining amphiphiles (see Figure 10)MD simulations showed that the increase in charge not only decreased the size of the micelle, as corroborated by experimental results, but also led to the formation of fewer total micelles.…”
Section: Secondary Interactions Used To Tune Assembled Morphologiesmentioning
confidence: 99%
“…DPD simulations are rapid and simple to implement compared to other coarse-grained simulations. As the integrated assumptions are paramount to accurate simulations, central to the success and accuracy of DPD simulations is the definition of the force fields. , …”
Section: Modeling Self-assemblymentioning
confidence: 99%
“…The number of papers on the soluble self-assembled polymeric particles is very high and we will discuss only a few of them in more detail, especially those addressing charged systems and exploiting explicit electrostatics. An interesting paper was recently published by Zhu et al [227]. The authors combined DPD with Split Reactive Brownian Dynamics (SRBD) [228], creating the Reactive DPD (RDPD), which enables the study of reacting systems.…”
Section: Experiment-inspired and Application-orientated Papersmentioning
confidence: 99%
“…I, for one, would be inclined towards a sharp no, but I think it is fair to concede that until we figure out in quantitative detail what kind of structures can emerge from the above equations, the question remains open. Interesting work along these lines is just beginning to appear [34].…”
Section: Self-catalytic Dpdmentioning
confidence: 99%
“…Figure 3: Reactive DPD simulation of a shape-changing vesicle under the effect of adsorption of solvophobic monomers (brown particles) at the outer region of the membrane. The chemical reactions at the outer membrane convert the solvophobic monomers into solvophilic ones, with a consequent hange in the shape of the vescicle.From[34].…”
mentioning
confidence: 99%